PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Vincensia Putri Bening Hardini, Suprihatmi Sri Wardiningsih & Lamidi (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze the effect of the competence of humanresources, motivation and work environment on employees performance. This study is asurvey on employees PT Sakura Garment Surakarta. Samples as many as 68 employeesby proportional cluster random sampling technique. Data collection technique usedquistionnaire and literature. Data were analyzed used multiple linear regression. Theresults showed that the competence of human resources have a significant effect onemployee performance. Motivation significant effect on employee performance. Theworking environment have a significant effect on employee performance. The coefficientof determination obtained value of adjusted R square of 0,518, this means that the effectof the competence of human resources, motivation and work environment on employeeperformance amounted to 51,8%, while by 48,2% influenced by other variables such asleadership, work discipline and organizational commitment.Keywords: competence, motivation, work environment, performance